An exploration into the parental identity of Filipino parents with disabilities Katty Kaye L.and Gabrielle Dominique Yngcong. - Saraza, Katty Kaye L.
There is a current lack of literature on the parental identity of parents with disabilities situated in a local context and the different factors, especially with regards to their disability identity, that may have a relation to parental identity. Thus, we aimed to answer how Filipino parents with disabilities form their parental identity. Using Gill's model of disability identity development and Piotrowski's adaptation of Crocetti's identity model into the parental identity domain for the framework, we aimed to explore how parents with disabilities' integration into society and to their disability community, how they integrate their sameness and differentness with others, and how they present and feel about themselves relate to how they commit, perform an in-depth exploration, or reconsider their commitment towards the parenting role. A basic qualitative design was used to explore how parents with disabilities form and make sense of their parental identity. Twelve (12) participants, with differing motor and physical disabilities , from Miagao and Capiz were interviewed using an interview schedule. Using thematic analysis, fourteen (14) themes emerged, answering each specific research question. Furthermore, the results imply that integration into society, a disability community, of their sameness and differentness, and of how they feel strengthens their parental identity. To conclude, an acceptance of their disability identity contributes to a stable parental identity. Implications of this study point towards the significance of promoting social inclusion of persons with disabilities into communities and societies and giving them opportunities to actively engage and participate in it. Keywords: parents with disabilities, parental identity, disability identity, parental identity of parents with disabilities